Analisis Konsistensi Mahmud Yunus Tentang Tidak Berhujjah Dengan Hadis Dhaif - Imam Suhada; Edi Safri; Zulfikri Zulfikri; Edriagus Saputra (Universitas Islam Negeri Imam Bonjol Padang, 2022)
The dhaif hadith is part of the lowest quality classification of hadith, because it has narrators who are not tsiqah or even contradicted by more tsiqah narrators. This study aims to analyze the consistency of Mahmud Yunus in not arguing with the dhaif hadith. The method in this research is descriptive-qualitative type in library research. The results of this study, namely Mahmud Yunus was very consistent in his argument that he did not use the dhaif hadith. This is evidenced by the hadiths contained in the discussion of his book and as evidence, the author traces the hadiths related to the based on the hadith of treating with alcohol, menstruating women enter the mosque and dissect corpses. All the hadiths contained in the discussion are of maqbul quality and none of the dhaif hadiths are used as evidence.